G (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1} ise, g (3) nedir?

G (x) = root [3] {x ^ {2} - 1} + 2 sqrt {x + 1} ise, g (3) nedir?
Anonim

Cevap:

#g (3) = 6 #

Açıklama:

Sadece her yerde 3 yerine # X #

#g (3) = kök (3) (3 ^ 2-1) + 2sqrt (3 + 1) #

#g (3) = kök (3) 8 + 2sqrt4 #

#g (3) = 2 + 2sqrt4 #

#g (3) = 2 + 2xx2 #

#g (3) = 2 + 4 #

#g (3) = 6 #

Cevap:

#g (3) 6 # =

Açıklama:

fiş #3# için # X #

#g (3) root3 (^ 02-01 Mart) + 2sqrt (3 + 1) # =

basitleştirmek

#g (3) (4) # root3 (9-1) + 2sqrt =

#g (3) root3 (8) + 2sqrt (4) # =

#g (3) = 2 + 2 (2) #

#g (3) = 2 + 4 #

#g (3) 6 # =